The third chemotaxis locus of Rhodobacter sphaeroides is essential for chemotaxis. - Porter, S; Warren, A; Martin, A; Armitage, J (2002)
The purple photosynthetic bacterium Rhodobacter sphaeroides has three loci encoding multiple homologues of the bacterial chemosensory proteins: 13 putative chemoreceptors, four CheW, four CheA, six CheY, two CheB and three CheR. Previously, studies have shown that, although deletion of cheOp1 led to only minor changes in behaviour, deletion of cheOp2 led to a loss of taxis. The third locus encodes two CheA, one CheR, one CheB, one CheW, one CheY, a putative cytoplasmic chemoreceptor (TlpT) and a protein showing homology to the chromosomal partitioning factor Soj (designated Slp). Here, we show that every protein encoded by this locus is essential for normal chemotaxis. Phototaxis is also dependent upon all the components of this locus, except CheB2 and Slp. The two putative CheA proteins encoded in this locus are unusual. CheA3 has only the P1 domain and the P5 regulatory domain linked by a large internal domain, whereas CheA4 lacks the P1 and P2 domains required for phosphorylation and response regulator binding. These data indicate that the minimal set of proteins required for normal chemotaxis in R. sphaeroides is all the proteins encoded by cheOp2 and the third chemotaxis locus, and that the multiple chemosensory protein homologues found in R. sphaeroides are not redundant.